Spiritual being and becoming : Western Christian and modern scientific cews of human nature for spiritual formation - Kyle, Eric J. (The Lutterworth Press, 2017)
As many as 100 billion neurons make up the human nervous system - a system that is incredibly complex, and a fundamental part of what makes us who we are. But there is far more to human beings than biology. Many academic disciplines study the human condition and there are many schools of thought within that study. We must also appreciate that the study of human nature did not begin in contemporary times. History is full of texts that offer detailed explorations of the human condition. However, no consensus has yet emerged. Consensus or not, those working towards religious and spiritual formation pursue the transformation of their communities. This book offers a fuller understanding of some of the common views of human nature and also insights into how we might utilize this knowledge in our ministries - ministries that strive towards the spiritual being and becoming of our world.